Feasibility and Morbidity of Magnetic Resonance Imaging-Guided Stereotactic Laser Ablation of Deep Cerebral Cavernous Malformations: A Report of 4 Cases. Issue 4 (16th July 2021) - Malcolm, James G; Douglas, J Miller; Greven, Alex; Rich, Christopher; Dawoud, Reem A; Hu, Ranliang; Reisner, Andrew; Barrow, Daniel L; Gross, Robert E; Willie, Jon T
Abstract: BACKGROUND: Magnetic resonance imaging (MRI)-guided laser interstitial thermal therapy (MRgLITT) has been used successfully to treat epileptogenic cortical cerebral cavernous malformations (CCM). It is unclear whether MRgLITT would be as feasible or safe for deep CCMs OBJECTIVE: To describe our experience with MRgLITT for symptomatic deep CCMs METHODS: Patients' records were reviewed retrospectively. MRgLITT was carried out using a commercially available system in an interventional MRI suite with efforts to protect adjacent brain structures. Immediate postoperative imaging was used to judge ablation adequacy. Delayed postoperative MRI was used to measure lesion volume changes during follow-up. RESULTS: Four patients with CCM in the thalamus, putamen, midbrain, or subthalamus presented with persistent and disabling neurological symptoms. A total of 2 patients presented with disabling headaches and sensory disturbances and 2 with recurrent symptomatic hemorrhages, of which 1 had familial CCM. Patients were considered by vascular neurosurgeons to be poor candidates for open surgery or had refused it. Multiple trajectories were used in most cases. Adverse events included device malfunction with leakage of saline causing transient mass effect in one patient, and asymptomatic tract hemorrhage in another. One patient suffered an expected mild but persistent exacerbation of baseline deficits. All patients showed improvement from a previously aggressive clinical course with lesion volume decreased by 20% to 73% in follow-up. CONCLUSION: MRgLITT is feasible in the treatment of symptomatic deep CCM but may carry a high risk of complications without the benefit of definitive resection. We recommend cautious patient selection, low laser power settings, and conservative temperature monitoring in surrounding brain parenchyma.